2014
DOI: 10.1159/000363429
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association Study of Angiotensin II Receptor Types 1 (A168G) and 2 (T1247G and A5235G) Polymorphisms in Breast Carcinoma among Brazilian Women

Abstract: Background: Many types of cancer are associated with polymorphisms of the renin-angiotensin system. Our aim was to assess possible association between single-nucleotide polymorphisms (SNPs) of the angiotensin II receptor types 1 (A168G), and 2 (T1247G and A5235G) with breast cancer. Patients and Methods: 242 participating subjects were genotyped and allocated to case or control groups. Results: Genotype distribution (in %) was: for AGTR1 (A168G): AA, AG, GG = 61, 30, 09 for cases, and 69, 25, 06 for controls (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Individuals harbouring genotypes with one or two copies of these allelic variants were found to be associated with 30% lower risk of BCa as compared to the homozygotes ( Koh et al, 2005 ). Conversely, another independent study showed no significant association between A168G polymorphism of AGTR1 and BCa risk, but demonstrated the significance of AGTR2 SNPs (T1247G and A5235G) as a predictor of BCa in Brazilian women ( Molina Wolgien Mdel et al, 2014 ). Nevertheless, deletion of the 5′ flanking region of AGTR1 showed 20-fold increase in chloramphenicol acetyltransferase reporter activity, thus confirming the presence of a negative regulatory element(s) in the upstream region of AGTR1 ( Takayanagi et al, 1994 ).…”
Section: Single Nucleotide Polymorphisms In Angii–agtr1 Pathwaymentioning
confidence: 94%
“…Individuals harbouring genotypes with one or two copies of these allelic variants were found to be associated with 30% lower risk of BCa as compared to the homozygotes ( Koh et al, 2005 ). Conversely, another independent study showed no significant association between A168G polymorphism of AGTR1 and BCa risk, but demonstrated the significance of AGTR2 SNPs (T1247G and A5235G) as a predictor of BCa in Brazilian women ( Molina Wolgien Mdel et al, 2014 ). Nevertheless, deletion of the 5′ flanking region of AGTR1 showed 20-fold increase in chloramphenicol acetyltransferase reporter activity, thus confirming the presence of a negative regulatory element(s) in the upstream region of AGTR1 ( Takayanagi et al, 1994 ).…”
Section: Single Nucleotide Polymorphisms In Angii–agtr1 Pathwaymentioning
confidence: 94%